The influence of social media marketing, consumer reviews, and brand image on purchasing decisions - Nabilla, Seikha; Saputro, Edy Purwo (Manajemen dan Bisnis, 2025)
This study explores the impact of social media marketing and online consumer reviews on purchasing decisions, with brand image as a mediating variable on TikTok. The research, conducted with 100 respondents who were active students in Indonesia and had made purchases via TikTok, used a quantitative approach and purposive sampling. Data analysis applied Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) method. The findings indicate that social media marketing and online consumer reviews both positively and significantly affect purchasing decisions and brand image. Furthermore, brand image plays a key role by mediating the relationship between social media marketing, online consumer reviews, and purchasing decisions. This study enriches existing literature by highlighting social media marketing and consumer reviews as essential factors shaping brand perception and purchasing behavior on TikTok. It supports the Theory of Planned Behavior (TPB), which emphasizes that attitudes, subjective norms, and perceived behavioral control influence consumer actions. From a practical standpoint, businesses can enhance their brand image and drive consumer decisions on TikTok by creating interactive, engaging content.